Dinâmica da dívida pública do Brasil: uma aplicação do modelo VAR estrutural - Bisognini, Kátia Vieira (2016)
The public debt sustainability is essential for the development and growth of a country. Countries that seek economic expansion in the short/medium term without maintaining a sustainable fiscal policy can incur to the problem of explosive trajectory of public debt, compromising their development and growth in the long term. This work aims to analyze the dynamics of Brazilian public debt through the structural vector autoregressive approach (SVAR) during the period of 2003 to 2015. For that, the model proposed by Apergis and Cooray (2015) to analyze the Greek public debt will be used as reference. However, adaptations were necessary to adequate the model to the Brazilian reality. Even if the adequacy of the model, the results obtained did not have adherence compatible with the economic theory, possibly due to the shocks that occurred in Brazil during this period. It is suggested the development of future studies to improve the model in order to get consistent results, like the reference model results.